Cultivation of Chlorella Sp. and Algae Mix for NH3-N and PO4-P Domestic Wastewater Removal - Suryawan, I Wayan Koko; Sofiyah, Evi Siti (Fakultas Teknik UB, 2020)
Domestic wastewater provides the largest contribution to pollution both in terms of quantity and quality. Therefore, before being discharged into the environment, wastewater needs to be managed first. This study used the cultivation of microalgae Chlorella Sp. and Algae Mix to manage domestic wastewater. The reactor used in the study was a 3L volume of water. The cultivation process was assisted by UV-A and UV-B with the air flow rate as much as 1.2L/min. Pollutant parameters being focused on were NH3-N and PO4-P nutrient parameters. Allowance for NH3-N by Chlorella sp. and algae mix are 54.9% and 49%, respectively. Allowance for PO4-P Chlorella sp. and algae mix is 70.2% and 57.1% while biomass increase of Chlorella Sp. and Algae Mix is 85.5% and 98.9%. Specific growth rate of Chlorella sp. and algae mix is 0.025 h-1 and 0.027 h-1. As a control on biomass growth, turbidity value in the study also increased.